LITERATUR ‘ULUM AL-QUR’AN ULAMA INDONESIA DAN TIMUR TENGAH: STUDI PERBANDINGAN KARYA AHSIN SAKHO MUHAMMAD DAN MANNA’ ALQATHTHAN - Nur Hazfira, Annisa; Mursyid, Ali (Asosiasi Dosen PTKIS Indonesia, 2022)
The discussion of the 'ulum Al-Qur'an is very broad, complicated, with Arabic literature that is difficult to understand. The existence of the book